2017
DOI: 10.18632/oncotarget.15842
|View full text |Cite
|
Sign up to set email alerts
|

Identifying biomarkers of papillary renal cell carcinoma associated with pathological stage by weighted gene co-expression network analysis

Abstract: Although papillary renal cell carcinoma (PRCC) accounts for 10%–15% of renal cell carcinoma (RCC), no predictive molecular biomarker is currently applicable to guiding disease stage of PRCC patients. The mRNASeq data of PRCC and adjacent normal tissue in The Cancer Genome Atlas was analyzed to identify 1148 differentially expressed genes, on which weighted gene co-expression network analysis was performed. Then 11 co-expressed gene modules were identified. The highest association was found between blue module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…Entry criteria do not include MET amplification or mutation, although tumor response by MET abnormality and expression level is being assessed. Furthermore, recent studies have looked at identifying biomarkers associated with the pathologic stage of PRCC (21). This is important as it has been shown that outcomes for PRCC, as well as being inferior to ccRCC, can be stratified into risk groups according to the International Metastatic Renal Cell Carcinoma Database Consortium prognostic model; the definition of additional biomarkers will only serve to strengthen such prognostic models (22).…”
Section: Discussionmentioning
confidence: 99%
“…Entry criteria do not include MET amplification or mutation, although tumor response by MET abnormality and expression level is being assessed. Furthermore, recent studies have looked at identifying biomarkers associated with the pathologic stage of PRCC (21). This is important as it has been shown that outcomes for PRCC, as well as being inferior to ccRCC, can be stratified into risk groups according to the International Metastatic Renal Cell Carcinoma Database Consortium prognostic model; the definition of additional biomarkers will only serve to strengthen such prognostic models (22).…”
Section: Discussionmentioning
confidence: 99%
“…Weighted gene coexpression network analysis (WGCNA) has been widely used to explore potential biomarkers of various diseases (Giulietti, Occhipinti, Principato, & Piva, ; Li et al, ; Wan, Tang, Han, & Wang, ; Yin, Cai, Zhu, & Xu, ). Similar studies selected only one interested phenotype for analysis, such as histologic grade (Clarke et al, ), pathological stage (He et al, ), metastasis (Tian, Guan, & Li, ), and so forth but very few studies had been done to analyze multiple phenotypes as we did, which could reduce the systemic bias that result from selecting a particular phenotype. In our study, the yellow modules were not only related to histologic grade ( r = 0.37; p = 1e−18), but also significantly correlated with pathological stage ( r = 0.32; p = 2e−14).…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma is one of the most common malignant carcinomas in the world and has a high incidence and mortality rate . In a previous study, we identified biomarkers of papillary renal cell carcinoma associated with pathological stage by weighted gene co‐expression network analysis . CcRCC is the most common type of renal cancer, and there is an urgent need to explore the mechanism of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…28 In a previous study, we identified biomarkers of papillary renal cell carcinoma associated with pathological stage by weighted gene coexpression network analysis. 29 CcRCC is the most common type of renal cancer, and there is an urgent need to explore the mechanism of the disease. LncRNA play important roles in tumor progression and may be biomarkers for clinical diagnosis and prognosis according to recent studies.…”
Section: Discussionmentioning
confidence: 99%